Battling the Chromolaena weed - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
The National Agricultural Research Institute (NARI) has declared war on the Chromolaena weed (Chromolaena odorata) in Papua New Guinea (PNG), and has won the first battle. Chromolaena is one of the most serious invasive weeds in the tropics